Study on Antibacterial Activities of Croton macrostachyus and Pycnostachys abyssinica Leaf Extracts Against Some Human Pathogens - Getahun Yemata; Endalamaw Yihune; Yewulsew Kebede (The Scientific World Journal)
The present study was aimed to verify the medicinal value of Croton macrostachyus and Pycnostachys abyssinica traditionally used to treat human and animal ailments in Ethiopia. Fresh leaves of these species were collected, dried under shade, and ground into fine powder. The extraction was carried out by the maceration method using methanol as a solvent. The compounds in the crude extract were further profiled by thin layer chromatography (TLC). The antibacterial activity of the compounds was evaluated using the agar well diffusion method. C. macrostachyus had a higher percentage extract yield (22.5%) than P. abyssinica (13.7%). The phytochemical screening showed more abundant phenolic compounds and tannins in the extract of C. macrostachyus and alkaloid, flavonoid, phenolic compounds, and tannins in the extract of P. abyssinica. Overall, C. macrostachyus produced twofold higher growth inhibition zone (24.0 ± 0.5–43.0 ± 1.0 mm) against the tested pathogens than P. abyssinica (7.0 ± 0.5–24.0 ± 0.3 mm). Among the bacteria, Klebsiella pneumoniae was found to be the most sensitive to compounds of C. macrostachyus. The lowest minimum inhibitory concentration (MIC) values (25 mg/mL) were obtained from compounds 1 and 3 of C. macrostachyus leaf extract against Escherichia coli and K. pneumoniae and compounds 2 and 3 of the same against S. aureus. Similarly, compound 1 of P. abyssinica leaf extract produced the lowest MIC (25 mg/mL) against K. pneumoniae and Staphylococcus epidermidis and compound 3 of the same species against E. coli and K. pneumoniae. All the profiled compounds of the two species had both bactericidal and bacteriostatic properties against the tested pathogens. The results of the present study revealed that the compounds of C. macrostachyus had strong antibacterial activity against all the tested pathogens, indicating the high potential of the compounds. However, further characterization and identification of the specific compounds for the development of biocide formulations are suggested.